Flexural versus dynamic processes of subsidence in the North American Cordillera foreland basin. Issue 16 (27th August 2013) - Painter, Clayton S.; Carrapa, Barbara
Abstract : [1] Dynamic subsidence related to subduction is an important process in retroarc foreland basin systems. Dynamic subsidence in the North American retroarc foreland has been proposed as dominant in the Late Cretaceous; however, questions remain about the nature of the subcrustal load and the basin response to such processes. We present new isopach data using 130 data points covering a large portion of the U.S. and a revised flexural analysis of the Sevier foreland. Higher rigidity associated with the Wyoming craton can best model flexural subsidence directly prior to ~81 Ma. We constrain the transition from flexural to nonflexural subsidence to ~81 Ma and correlate this with large Late Cretaceous progradation. The locus of subsidence and the location of the subducted Shatsky oceanic plateau suggest that dynamic loading from viscous flow above the subducting plate is the mechanism driving dynamic subsidence in the retroarc foreland basin of the North American Cordillera. Key Points: Isopachs constrain transition from flexural to non‐flexural subsidence Flexural model tests rigidity of the Wyoming Province Dynamic processes responsible for non‐flexural subsidence